Comparison between Enzyme Immunoassays Performed on Samples of Dried Blood and Serum for Toxoplasmosis Prenatal Screening: Population-based Study - Bárbara Araújo Marques; Ericka Vianna Machado Carellos; Vânia Maria Novato Silva; Fernando Henrique Pereira; Maria Regina Lage Guerra; Jacqueline Araújo Domingos Iturra; José Nélio Januário; Gláucia Manzan Queiroz de Andrade (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2021)
Abstract Objective Most prenatal screening programs for toxoplasmosis use immunoassays in serum samples of pregnant women. Few studies assess the accuracy of screening tests in dried blood spots, which are of easy collection, storage, and transportation. The goals of the present study are to determine the performance and evaluate the agreement between an immunoassay of dried blood spots and a reference test in the serum of pregnant women from a population-based prenatal screening program for toxoplasmosis in Brazil. Methods A cross-sectional study was performed to compare the immunoassays Imunoscreen Toxoplasmose IgM and Imunoscreen Toxoplasmose IgG (Mbiolog Diagnósticos, Ltda., Contagem, Minas Gerais, Brazil)in dried blood spots with the enzymelinked fluorescent assay (ELFA, BioMérieux S.A., Lyon, France) reference standard in the serum of pregnant women from Minas Gerais Congenital Toxoplasmosis Control Program. Results The dried blood spot test was able to discriminate positive and negative results of pregnant women when comparedwith the reference test, with an accuracy of 98.2% for immunoglobulin G (IgG), and of 95.8% for immunoglobulin M (IgM). Conclusion Dried blood samples are easy to collect, store, and transport, and they have a good performance,making this a promisingmethod for prenatal toxoplasmosis screening programs in countries with continental dimensions, limited resources, and a high prevalence of toxoplasmosis, as is the case of Brazil.